A STUDY ON CORELATION BETWEEN PEER SUPPORT GROUPS AND QUALITY OF LIFE IN PEOPLE LIVING WITH HIV/AIDS IN BANDUNG CITY - Novianti, Wini Resna; Oktavia, Bioseffa; Jayanti, Tri Nur; Rustikayanti, R Nety (Jurnal Medika Cendikia, 2023)
The Human Immunodeficiency Virus (HIV) is a virus that attacks the human immune system, leading to Acquired Immune Deficiency Syndrome (AIDS). AIDS emerges after the HIV virus has attacked the immune system for five to ten years or more in individuals affected by HIV. One of the factors related to HIV/AIDS is quality of life, which is essential for the well-being of People Living with HIV/AIDS (PLWHA). Peer group support is one of the factors influencing quality of life. This study aims to explore the relationship between Peer Group Support and Quality of Life among individuals with HIV/AIDS in the city of Bandung. The research was conducted in July 2023, with a sample size of 49 respondents selected using purposive sampling technique. Data was analyzed using the chi-square test, resulting in a p-value of 0.03, indicating a significant relationship between peer group support and quality of life among individuals with HIV/AIDS. Peer support groups can impact the quality of life of PLWHA, as they require external factors to enhance their quality of life, one of which is derived from peer group support. Further research is expected to analyze various variables to identify factors influencing the quality of life of individuals with HIV/AIDS.